2014
DOI: 10.1111/pce.12340
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile emissions from the soil

Abstract: Volatile compounds are usually associated with an appearance/presence in the atmosphere. Recent advances, however, indicated that the soil is a huge reservoir and source of biogenic volatile organic compounds (bVOCs), which are formed from decomposing litter and dead organic material or are synthesized by underground living organism or organs and tissues of plants. This review summarizes the scarce available data on the exchange of VOCs between soil and atmosphere and the features of the soil and particle stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
327
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(334 citation statements)
references
References 299 publications
(337 reference statements)
3
327
1
3
Order By: Relevance
“…α-pinene and Δ 3 -carene, emissions from ground level may vary with litter quality and quantity, soil microbial activity and physiological stages of plants (Warneke et al, 1999;Insam and Seewald, 2010;Aaltonen et al, 2011;Penuelas et al, 2014). Previous work in the tropical forest in has indicated that Atmos.…”
Section: Vertical Gradient In No 3 Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…α-pinene and Δ 3 -carene, emissions from ground level may vary with litter quality and quantity, soil microbial activity and physiological stages of plants (Warneke et al, 1999;Insam and Seewald, 2010;Aaltonen et al, 2011;Penuelas et al, 2014). Previous work in the tropical forest in has indicated that Atmos.…”
Section: Vertical Gradient In No 3 Reactivitymentioning
confidence: 99%
“…The resulting β-caryophyllene mixing ratios lie between 10 and 60 pptv, which, based on a rate constant of 1.9 × 10 -11 cm 3 molecule -1 s -1 , results in a contribution to NO 3 reactivity of up to 0.03 s -1 . As β-caryophyllene emissions from pine tree needles reveals a strong temperature dependence (Hakola et al, 2006) it seems unlikely that this is an important source of β-caryophyllene during 5 the relatively cold September nights of the IBAIRN campaign and its emissions from other sources, especially those at ground level including soil may be more important (Insam and Seewald, 2010;Penuelas et al, 2014).…”
Section: Of the Supplementary Information) While The 10mentioning
confidence: 99%
“…They are formed mainly by oxidation of glucose from various intermediates (Korpi et al, 2009). The underlying biosynthetic pathways are aerobic, heterotrophic carbon metabolism, fermentation, amino-acid catabolism, terpenoid biosynthesis, fatty acid degradation and sulphur reduction (Peñuelas et al, 2014). The main metabolic pathways for microbial volatiles are summarised in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on the ecological role of volatiles in microbe-microbe interactions. For more information on techniques used for volatile analyses and their role in microbe interactions with their eukaryotic hosts, we refer to several recent reviews (Effmert et al, 2012;Farag et al, 2013;Junker and Tholl, 2013;Peñuelas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This may include releasing a blend of specific floral volatile scents that attract predators of herbivores after being attacked (Kessler 2010;Peñuelas et al 2014)). In the model plant Arabidopsis, females of parasitoids Cotesia marginiventris use TPS10 (a sesquiterpene) to track their lepidopteran host by utilizing the floral scent (Schnee et al 2006).…”
Section: Terpenoid Volatiles: An Immediate Response In Plant Defensementioning
confidence: 99%